Linear and nonlinear relationship of wheat storage characteristics - Kiurchev, S.; Verholantseva, V. (My University, 2015)
EN: The article deals with the linear and nonlinear dependencies that predict performance of wheat storage at certain temperatures and storage period. Such parameters of wheat quality as gluten and gluten deformation index after cooling in the granary were determined. Indicators at different temperatures during storage of grain were compared. Experimental data have been processed in Math Cad. Experimental and theoretical values have been analyzed. We came to the conclusion that values deviations are minor, so obtained mathematical model is adequate and enables to predict grain yield depending on the storage temperature with sufficient degree of accuracy. Presented linear and curvilinear relationships between gluten and wheat gluten deformation index allow predicting the technological parameters that affect the quality of gluten. The models equations of linear and nonlinear dependence for gluten and gluten deformation index are presented. The obtained results showed that cooling used in a granary makes it possible to improve the technological parameters that define baking properties of wheat grain particularly the quantity and quality of gluten.
Keywords: gluten; quality; storage parameters; the matrix of correlation coefficients; factors; optimization